2018
DOI: 10.1101/434001
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

One Health genomic surveillance ofEscherichia colidemonstrates distinct lineages and mobile genetic elements in isolates from humans versus livestock

Abstract: Running title: One Health genomic surveillance of Escherichia coli 25 2 ABSTRACT 26 Livestock have been proposed as a reservoir for drug-resistant Escherichia coli that infect 27 humans. We isolated and sequenced 431 E. coli (including 155 ESBL-producing isolates) 28 from cross-sectional surveys of livestock farms and retail meat in the East of England. These 29 were compared with the genomes of 1517 E. coli associated with bloodstream infection in the 30 United Kingdom. Phylogenetic core genome comparisons de… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 49 publications
3
15
0
Order By: Relevance
“…Whilst unpublished, the other plasmid (pTC_N40607) has been identified in E. coli in the USA so is likely to be similarly widespread. Accordingly, whilst there is some evidence of shared circulating plasmids, as reported in a number of recent studies (3537), the overall level of overlap between farm and human bla CTX-M E. coli identified in this study was very small and not suggestive of any novel or recent transmission events.…”
Section: Discussionsupporting
confidence: 55%
“…Whilst unpublished, the other plasmid (pTC_N40607) has been identified in E. coli in the USA so is likely to be similarly widespread. Accordingly, whilst there is some evidence of shared circulating plasmids, as reported in a number of recent studies (3537), the overall level of overlap between farm and human bla CTX-M E. coli identified in this study was very small and not suggestive of any novel or recent transmission events.…”
Section: Discussionsupporting
confidence: 55%
“…13 However, recent reports suggest that such transmission is very limited, at least in the UK. 14 In dairy farming, antibiotics are used both therapeutically in the treatment of common infections such as mastitis, and preventatively e.g. in so-called dry cow therapy, an antibacterial preparation inserted into a cow’s udder between lactations to prevent against mastitis.…”
Section: Introductionmentioning
confidence: 99%
“…One-Health studies applying massive-parallel and single-molecule sequencing conform a good approximation to try to understand how antibiotic resistances flow between human-animal-environment scenario. There are different One-Health studies were Illumina 64 and Nanopore 65 or PacBio 66 sequencing are used together to characterize bacteria isolated from different sources and try to unveil if there is relation amongst them. For example, in 2018, Ludden et al 64 performed a study in which concluded that there were similar antibiotic resistances between livestock and human E. coli, conferring resistance to 4 type of antibiotics, but on the other hand there was not a close relation between E. coli isolated from livestock and E. coli causing infection in human.…”
Section: Discussionmentioning
confidence: 99%